Integrative Analysis of lncRNA-mRNA Co-expression Provides Novel Insights Into the Regulation of Developmental Transitions in Female Varroa destructor - Wu, Jiang-Li; Hu, Ruo-Yang; Li, Nan-Nan; Tan, Jing; Zhou, Chun-Xue; Han, Bin; Xu, Shu-Fa (Frontiers in Ecology and Evolution, 2022)
Varroa destructor is a major pathogenic driver of the Western honeybee colony losses globally. Understanding the developmental regulation of V. destructor is critical to develop effective control measures. Development is a complex biological process regulated by numerous genes and long non-coding RNAs (lncRNAs); however, the underlying regulation of lncRNAs in the development of V. destructor remains unknown. In this study, we analyzed the RNA sequencing (RNA-Seq) data derived from the four stages of female V. destructor in the reproductive phase (i.e., egg, protonymph, deutonymph, and adult). The identified differentially expressed mRNAs and lncRNAs exhibited a stage-specific pattern during developmental transitions. Further functional enrichment established that fat digestion and absorption, ATP-binding cassette (ABC) transporters, mitogen-activated protein kinase (MAPK) signaling pathway, and ubiquitin-proteasome pathway play key roles in the maturation of female V. destructor. Moreover, the lncRNAs and mRNAs of some pivotal genes were significantly upregulated at the deutonymph stage, such as cuticle protein 65/6.4/63/38 and mucin 5AC, suggesting that deutonymph is the key stage of metamorphosis development and pathogen resistance acquisition for female V. destructor. Our study provides novel insights into a foundational understanding of V. destructor biology.